Risk of sexual, physical and verbal assaults on men who have sex with men and female sex workers in coastal Kenya. (December 2015) - Micheni, Murugi; Rogers, Sam; Wahome, Elizabeth; Darwinkel, Marianne; van der Elst, Elise; Gichuru, Evans; Graham, Susan M.; Sanders, Eduard J.; Smith, Adrian D.
Abstract : Background: Violence toward MSM and female sex workers (FSW) is associated with HIV risk, and its prevention is prioritized in international HIV/AIDS policy. Methods: Sociodemographic and behavioural data derived from HIV risk and follow-up cohorts including MSM and FSW in coastal Kenya between 2005 and 2014 was used to estimate the risk of rape, physical assault and verbal abuse, and to assess associations between first occurrence of assault with individual and recent behavioural factors. Results: Incidence of first reported rape was similar for MSM [3.9, confidence interval (CI) 3.1–5.0 per 100 person-years (pyrs)] and FSW (4.8 CI 3.5–6.4 per 100 pyrs), P = 0.22. Incidence of first reported physical and verbal assault was higher for FSW than MSM (21.1 versus 12.9 per 100 pyrs, P = 0.14 and 51.3 versus 30.9 per 100 pyrs, P = 0.03 respectively). Recent alcohol use was associated with reporting of all forms of assault by MSM [adjusted odds ratio (AOR) 1.8, CI 0.9–3.5] and FSW (AOR 4.4, CI 1.41–14.0), as was recent sale of sex for MSM (AOR 2.0, CI 1.1–3.8). Exclusive sex with men, active sex work, and group sex were also specifically associated with reporting rape for MSM. Perpetrators of sexual and verbal assault were usually unknown, whilst perpetrators of physical violence toward FSW were usually regular sexual partners. Conclusion: MSM and FSW experienced a similarly high incidence of sexual assault in coastal Kenya, in addition to physical and verbal assault. Current national policies focus heavily on gender-based violence against women and young girls, but need to be inclusive of MSM and FSW.